2021
DOI: 10.1371/journal.ppat.1009683
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, reliable, and reproducible cell fusion assay to quantify SARS-Cov-2 spike interaction with hACE2

Abstract: COVID-19 is a global crisis of unimagined dimensions. Currently, Remedesivir is only fully licensed FDA therapeutic. A major target of the vaccine effort is the SARS-CoV-2 spike-hACE2 interaction, and assessment of efficacy relies on time consuming neutralization assay. Here, we developed a cell fusion assay based upon spike-hACE2 interaction. The system was tested by transient co-transfection of 293T cells, which demonstrated good correlation with standard spike pseudotyping for inhibition by sera and biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…(E) Effect of cobicistat treatment on S-glycoprotein-mediated fusion. TZM-bl cells stably expressing the S-glycoprotein were incubated with different concentrations of cobicistat for 1 h and mixed with cells stably expressing human ACE2 ( 40 ). Cell fusion was assessed by measuring firefly luciferase activity after 24 h. RLU, relative light units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(E) Effect of cobicistat treatment on S-glycoprotein-mediated fusion. TZM-bl cells stably expressing the S-glycoprotein were incubated with different concentrations of cobicistat for 1 h and mixed with cells stably expressing human ACE2 ( 40 ). Cell fusion was assessed by measuring firefly luciferase activity after 24 h. RLU, relative light units.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to obtain a specific and quantitative estimate of the impact of cobicistat on the S-glycoprotein–ACE2 interaction, we tested the effect of this drug using a previously validated fusion assay ( 40 ) based on cell lines stably transfected with the S-glycoprotein and human ACE2. The results showed that cobicistat can inhibit S-glycoprotein fusion with an IC 50 of 3.8 μM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report showed that LCB1, a miniprotein SARS-CoV-2 inhibitor, can effectively inhibit cell fusion by co-incubating with SARS-CoV-2 at −1 and 0 h before adding the mix to Vero cells. 38 Here, we mixed different concentrations of the D-peptides with 100 TCID 50 of the SARS-CoV-2 isolates for 30 min at 37 °C before incubating the mix with the cells. Therefore, we did not expect to see a different mechanism of action for our designs if we preincubated these peptides with the virus during a similar time range.…”
Section: Discussionmentioning
confidence: 99%
“…To delineate whether brilacidin blocks SARS‐CoV‐2 viral entry, we generated pseudotyped HIV‐1‐derived lentiviral particles with SARS‐CoV‐2 spike protein, 35 which is widely used to study spike‐mediated viral entry into host cells in biosafety Level 2 facilities. 40 , 41 Brilacidin was tested in SARS‐CoV‐2 pseudovirus entry assay in several ACE2‐expressing cell lines including Vero C1008, Calu‐3, Huh‐7, Caco‐2, and 293T‐ACE2. Vero C1008 and 293T‐ACE2 express minimal levels of transmembrane serine proteinase 2 (TMPRSS2), therefore the SARS‐CoV‐2 virus enters into these cell lines mainly through endocytosis and relies on endosomal cathepsin L for viral spike protein activation.…”
Section: Resultsmentioning
confidence: 99%